2020
DOI: 10.2337/db20-1064-p
|View full text |Cite
|
Sign up to set email alerts
|

1064-P: The Human Recombinant REG3A Protein ALF-5755 Restores Glucose Homeostasis and Insulin Sensitivity in High-Fat Fed Mice and in Ob/Ob Mice

Abstract: Introduction: REG3A (Regenerating islet-derived protein 3A) is a carbohydrate-binding protein belonging to the family of C-type lectins. REG3A has antioxidant and anti-inflammatory properties modulating glucose and lipid homeostasis. We report a study of the effects of the administration of the human recombinant REG3A protein ALF-5755 on glucose and lipid homeostasis in insulin-resistant mice. Materials and Methods: 4-week-old C57Bl/6N male mice were fed HFD for 12 weeks. The control group recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies have shown the role of and the requirement of Reg new islet formation in aging and high‐fat diet induced obesity and the role of Reg in restoring glucose homeostasis in obesity in animal models. 50 , 51 Studies have shown the reversal of diabetes with Reg proteins and shorter peptides in preclinical mammalian studies. 52 , 53 …”
Section: The Role Of Reg In Regenerationmentioning
confidence: 99%
“…Studies have shown the role of and the requirement of Reg new islet formation in aging and high‐fat diet induced obesity and the role of Reg in restoring glucose homeostasis in obesity in animal models. 50 , 51 Studies have shown the reversal of diabetes with Reg proteins and shorter peptides in preclinical mammalian studies. 52 , 53 …”
Section: The Role Of Reg In Regenerationmentioning
confidence: 99%